2020
DOI: 10.3390/ani10020349
|View full text |Cite
|
Sign up to set email alerts
|

Diet Supplementation with a Bioactive Pomace Extract from Olea europaea Partially Mitigates Negative Effects on Gut Health Arising from a Short-Term Fasting Period in Broiler Chickens

Abstract: The effects of supplementing chicken diets with an olive pomace extract (OE) from Olea europaea on performance and gut health after a challenge of intestinal permeability (IP) increase were studied. Treatments included a control diet with no additives (CF), and diets supplemented with 100 ppm of monensin (MF) or with 500 (OE500F) and 1500 ppm (OE1500F) of an OE. At 14 d, all birds, except those allocated in a control group (CNF), were submitted to a 15.5 h short-term fasting period to induce IP increase. Fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Short-term FP up to 24 h has been reported to increase intestinal permeability (38), which may potentially induce bacterial translocation (39), lameness (40), and compromised growth performance (41). A recent study conducted by Herrero-Encinas et al (31) showed that a 15.5-h short-term FP induced an increase in intestinal permeability by reducing Claudin-1 expression, which triggered an inflammatory response, resulting in a higher CD and lower VH:CD ratio compared to control nonfasted group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term FP up to 24 h has been reported to increase intestinal permeability (38), which may potentially induce bacterial translocation (39), lameness (40), and compromised growth performance (41). A recent study conducted by Herrero-Encinas et al (31) showed that a 15.5-h short-term FP induced an increase in intestinal permeability by reducing Claudin-1 expression, which triggered an inflammatory response, resulting in a higher CD and lower VH:CD ratio compared to control nonfasted group.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, a short-term FP was performed by removing feeders for 16 h and 30 min. This aimed to induce a challenge, as this practice has been reported as a model to increase intestinal permeability and thereby negatively affect the gut integrity (31).…”
Section: Short-term Fasting-induced Challengementioning
confidence: 99%
“…(2017) where resveratrol increased MUC-2 expression and goblet cell concentrations. A lack of effect on IP has also been observed for olive pomace under the 15.5 h fasting model ( Herrero-Encinas et al., 2020 ). It would have been interesting to study the effect of olive pomace feeding after fasting, but it was not studied.…”
Section: Dietary Interventions To Reduce Intestinal Permeabilitymentioning
confidence: 82%
“…Modern meat-type chickens have been bred for high feed intake and growth, therefore keeping them off-feed can also induce stress with consequences on intestinal function including an increased IP. Fasting has been shown to increase IP in chickens measured by L:M, L:R ratios or FITC-d. Fasting of 4.5 and 9 h ( Gilani et al., 2018a ), 15.5 h ( Herrero-Encinas et al., 2020 ) and 24 h ( Vicuña et al., 2015b ) have shown to induce a GIT leakage. In addition to FITC-d and L:M ratio markers, claudin-3 and fatty acid binding protein (FABP) were significantly reduced in 4.5 and 9 h fasted chickens suggesting TJ modulation as well ( Gilani et al., 2018c ).…”
Section: Experimental Models To Increase Intestinal Permeability Based On Disease Challenges and Various Stress Factorsmentioning
confidence: 99%
See 1 more Smart Citation